FAMILY COST EFFICIENCY WITH THE UTILIZATION OF LIQUID ORGANIC FERTILIZER WITH PHYTOHORMONES IN ENSURING COMMUNITY NUTRITION IMPROVEMENT THROUGH PLANTING ORGANIC VEGETABLES IN THE YARD - Rusdiyanto, Edi; Munawir, Abdillah (LPPM Univ. Ibn Khaldun Bogor, 2024)
The purpose of this service is to cultivate organic vegetable plants in the yard so as to minimize family income and the application of liquid organic fertilizer using household kitchen spices or onion peels which are considered waste and household waste that is always discharged into the environment. The method used is Participatory Learning through Participatory Community partners with discussion, practice and demonstration materials. The results of this service increase the awareness of farmer groups and housewives and the community the importance of developing vegetable cultivation around the yard of the house, especially can increase income from selling vegetables and reduce family expenses in shopping organic vegetables for family needs. In making organic liquid fertilizer using waste or onion peels into organic liquid fertilizer, it is felt directly by partners and housewives and provides knowledge about the importance of onion peels and no longer throws onion peels into the environment which is considered household manure.